APPLICATION OF THE NTU-18 TURBIDITY DEVICE FOR REAL-TIME RIVER SEDIMENTATION MONITORING (Jurnal Teknologi (Sciences & Engineering), 2025)
The NTU-18 turbidity sensor tool is used for sediment measurement so that the process can be done more easily and practically. The purpose of this study is to analyze and calculate the distribution of sediment using the Reuse equation based on the measurement results with the NTU-18 turbidity sensor tool at a certain point in the Way Khilau watershed. The method used is the Reuse equation. Measurement data is used to calculate particle fall velocity and Reuse parameters. Sediment concentration was calculated with the depth of the reference surface increased by 0.05 m until it approached the depth of the riverbed. The sediment distribution ratio is calculated at each depth and the result is a graph of the relationship between the sediment distribution ratio and the average concentration value at the reference surface depth. Then the amount of sediment in the Way Khilau watershed can be approximated by the equation y = 502,58 X2 – 1017,4 X + 514,85 to y = 604,12 X2 – 1228,8 X + 624,81. The sediment distribution graph shows that sediments in the Way Khilau watershed tend to be bed load. This occurs because of the relatively low flow velocity in the Way Khilau watershed. The conclusion is that the amount of sedimentation in the Way Khilau watershed can be estimated using the Reuse equation, although only with certain point data and can be calculated the amount of sediment at all river depths.Keywords: Suspended Sediment, Sediment Estimator, NTU-18, Sediment Distribution, Reuse